Iodine Deficiency Disorders in the Iodine-Replete Environment - Nyenwe, Ebenezer A. (2009)
BACKGROUND: Iodine deficiency disorders (IDD) constitute significant public health problems in parts of the world with poor iodine nutrition, but have been eradicated in North America and other regions. We herein report three cases of iodine deficiency disorders (IDD) which occurred in women living in iodine-replete environments. METHODS: The clinical presentation, biochemical findings, and radiological features of the patients were analyzed and presented in three case reports. The radiological features are illustrated in sonographic and scintigraphic images. A literature review and discussion which highlight the risk factors, pathogenesis, ancillary investigations and rational treatment of iodine deficiency goiter and hypothyroidism are provided. RESULTS: All of our three patients were young females, aged 24–38 years, who had goiter. Two of them presented with goitrous hypothyroidism. Radioactive iodine scintigraphy showed a characteristic finding of diffusely increased uptake (in the absence of clinical and biochemical evidence of hyperthyroidism). This scintigraphic pattern was found to be pathognomonic. Dietary iodine supplementation alone resulted in complete remission of IDD in the subjects, including the two patients with hypothyroidism. CONCLUSION: IDD can occur in iodine replete-environments. A high index of suspicion is needed to recognize these cases. It is pertinent that the correct diagnosis be made to avoid unwarranted life-long thyroxine therapy in patients presenting with goiter and hypothyroidism, which is easily treatable with iodized salt. These cases underscore the need for considering iodine deficiency in the etiologic diagnosis of goiter and hypothyroidism, even in iodine sufficient regions.